Formação inicial em pedagogia no contexto da crise estrutural do capital - Silva, Iara Rute Morais de Oliveira da (2024)
The understanding of the ontological dimension of education and its relationship with labor is essential to grasp the essence of teacher training in capitalist society. The research main goal is to analyze the impacts of the structural crisis of capital on the initial training of Pedagogy students. In order to do so bibliographic-documentary research was carried out based on the foundations of Lukácsian-marxism. To understand the social context students belong to, authors who analyze and investigate capitalist society and the structural crisis of capital were chosen, among which: Marx (2014), Lukács (2013), Mészáros (1998), Antunes (2009), Tonet (2016, 2017), Tonet and Lessa (2011). Regarding teacher training in Brazil and the influence of the crisis of capital on education, a historical contextualization was necessary aiming at understanding how political ruptures and fluctuations in the State apparatus reflect in teacher training in Brazil. Aranha (2012), Saviani (2009, 2012, 2019), Mendes Segundo et al. (2015), Mendes Segundo and Jimenez, 2015 are some of the authors who support this comprehension. In the last chapter, Rabelo and Leitão (2015), do Carmo, Gonçalves and Mendes Segundo (2015), Araújo (2024) helped us analyze the movement that took place in Jomtien, Thailand, in the 1990s, called Education for All (EFA) and how this event affected Brazilian education and teacher training. They also assisted with unveiling important documents, such as the report Learning: the treasure within (1993), Declaração de Brasília (2004), Lei de Diretrizes e Bases da Educação (LDB), Parâmetros Curriculares Nacionais (PCNs), Base Nacional Curricular (BNC-Formação), Diretrizes Curriculares do Curso de Pedagogia, Projeto Político Pedagógico do Curso de Pedagogia (UECE and UFC) which guide Pedagogy undergraduate degree courses and teacher training in Brazil. The examination allows us to infer that the capitalist system transformed education in commodity, causing its commodification. That deeply affects teacher training and encourage the privatization of schools and higher education which, in turns, creates a space favorable to the unbridled expansion of private institutions and online undergraduate education courses. A scenario that threatens training and qualification of teachers. Education solely cannot contribute to ending the problems caused by capital, but its contribution is fundamental. A critical reasoning of the training processes that guide the initial training of teachers nowadays in Brazil and the role these professionals play are imperative factors towards social emancipation.